A rare case of esophageal lymphangioma associated with gastric adenocarcinoma - Mesut BAŞAK,; Ahmet Kemal GÜRBÜZ,; Mehmet Amin ÖNDE,; Zeki ÇANKIR,; Özcan KESKİN,; Yusuf YAZGAN,; Levent DEMİRTÜRK,; Mehmet DANACI, (Turkish Journal of Gastroenterology, 2019)
-